HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS V SEKOLAH DASAR GUGUS I KECAMATAN TAMPAN PEKANBARU - Kartina '; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Emotional intelligence is one of the factors that affect the learning process of students. To know the extent to which has achieved the objectives of learning then required assessment of learning outcomes. The purpose of this study is to determine the correlation of emotional intelligence with the results of learning Indonesian of students. Emotional intelligence is the ability to motivate own self and survive from frustration, controlling impulse, and not exaggerating pleasure, managing moods and keeping stress burden not crippling the ability to think, empathize and pray. The components that exist in emotional intelligence are emotional self-awareness, managing emotions, utilizing emotions productively, empathy and foster relationships. This study is a quantitative research, the instrument used in the form of questionnaires and documentation of learning outcomes of even UTS (Mid Term) in the end of semester (2nd semester) period of learning 2016-2017 on the subjects of the Indonesian language. The data obtained from this study is that there is a correlation between emotional intelligence with learning result of Indonesian language subject the 5th grade student of elementary school group 1 Subdistrict Tampan Pekanbaru as much as 0,501. Medium relationship level and also emotional intelligence give influence to learning result of Indonesian language equal to 25% and 75% determined by other factor.Keyword: Emotional intelligence, learning result of Indonesian language subject.